2015
DOI: 10.1097/hrp.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Tobacco Use Disorders in Smokers with Serious Mental Illness

Abstract: Addiction to tobacco-derived nicotine remains highly prevalent in the US, with 18% using daily, but 53% of those with serious mental illness smoke regularly. While smokers with serious mental illness have been excluded from most large nicotine dependence treatment studies, a growing evidence base is emerging to guide clinicians in how to assist their patients with psychiatric illness to quit smoking. The aim of this review is to present the evidence on safety and efficacy of smoking cessation interventions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
70
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 75 publications
(147 reference statements)
5
70
0
10
Order By: Relevance
“…16,24,25 A recent thorough review by the European Psychiatric Association reported that current smoking cessation treatments are useful, but not highly efficacious, for smokers with schizophrenia. 26 Based on these prior studies, recommendations for treating smoking in schizophrenia include the use of bupropion or varenicline (with or without nicotine replacement therapy [NRT]) in combination with behavioral treatment 24,[27][28][29] ; we sought to support and expand upon these recommendations. Specifically, we performed a pilot study to examine the rapid (within 2 weeks) initiation of a combination of first-line treatments (COMB) administered for an extended period of time (EXT; 6 months) with or without home visits (HV) for smokers with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…16,24,25 A recent thorough review by the European Psychiatric Association reported that current smoking cessation treatments are useful, but not highly efficacious, for smokers with schizophrenia. 26 Based on these prior studies, recommendations for treating smoking in schizophrenia include the use of bupropion or varenicline (with or without nicotine replacement therapy [NRT]) in combination with behavioral treatment 24,[27][28][29] ; we sought to support and expand upon these recommendations. Specifically, we performed a pilot study to examine the rapid (within 2 weeks) initiation of a combination of first-line treatments (COMB) administered for an extended period of time (EXT; 6 months) with or without home visits (HV) for smokers with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…73 So too is pharmacotherapy alone or in combination with counselling or motivational inter-viewing. [74][75][76] Mobile phone-based support and internet-assisted cessation is effective in general populations, but these interventions have not been well studied in smokers with serious mental illness. [77][78][79] It is unclear which smoking cessation options are best for people with serious mental illness, but the limited evidence suggests that those that are effective for smokers in the general population are also effective for smokers with serious mental illness, with or without comorbid substance abuse disorders.…”
Section: Smoking Cessation In People With Serious Mental Illnessmentioning
confidence: 99%
“…Isso pode ser uma das razões pela quais os pacientes com TPD morram 25 anos antes da população em geral. As taxas de tabagismo excepcionalmente elevadas entre estes indivíduos poderiam contribuir direta ou indiretamente para as altas taxas de morbidade e mortalidade (Evins et al, 2015).Pessoas com depressão grave, distúrbios relacionados ao álcool e à esquizofrenia têm altas taxas de mortalidade devido a doenças vasculares e câncer (Evins et al, 2015).Fumar também complica o tratamento de alguns TPD, reduzindo os níveis sanguíneos de neurolépticos. Portanto, os fumantes podem necessitar de doses mais 24 elevadas para alcançar um efeito terapêutico, e podem apresentar um risco aumentado de efeitos secundários de drogas (Lasser et al, 2000).…”
unclassified
“…O progresso no desenvolvimento de tratamento para tabagismo nesse grupo tem sido lento, em parte porque a maioria dos fumantes com TPD ainda estão excluídos de grande parte dos ensaios de cessação do tabagismo e de estudos de validação diagnóstica (Hitsman et al, 2009). Infelizmente existe um certo preconceito quanto à abordagem do tabagismo no campo da psiquiatria (Ziedonis et al, 2008;Morisano et al, 2009;Hitsman et al, 2009;Evins et al, 2015). Muitas falsas percepções como a crença de que a cessação é impossível e de que os pacientes com TPD não querem parar de fumar são bem comuns (Morisano et al, 2009;Hitsman et al, 2009).…”
unclassified
See 1 more Smart Citation